Fenomena Pekerja Anak pada Perkebunan Kelapa Sawit di Wilayah Perbatasan Kabupaten Sambas, Kalimantan Barat - Atem Atem (Raheema, 2019)
A child has become a significant object to face many problems, especially social problems which often rise along with the development of this country. The children workers being a problem in Indonesia which is caused by the expanding of industrial markets such as palm oil industry. Moreover, a large number of palm oil plantation in some areas could reach the border is as well. In Sambas regency, for instance, there are so many palm oil industries that entangle children as workers. This research, furthermore, aims to explore and describe the children workers phenomenon in Sambas, West Kalimantan, through the qualitative and quantitative method of the literature study.